2016
DOI: 10.1111/jdv.13851
|View full text |Cite
|
Sign up to set email alerts
|

The three moments of skin cream application: an evidence‐based proposal for use of skin creams in the prevention of irritant contact dermatitis in the workplace

Abstract: Contact dermatitis is one of the most common occupational diseases, with serious impact on quality of life, lost days at work and a condition that may be chronically relapsing. Regular prophylactic skin cream application is widely acknowledged to be an effective prevention strategy against occupational contact dermatitis; however, compliance rates remain low. To present a simple programme for skin cream application in the workplace with focus on implementation to drive down the rate of occupational irritant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In The Netherlands, the guidelines on the prevention of contact dermatitis recommend the use of emollients on a regular basis, and creams are often provided by the employer . Similar recommendations have been proposed by the working group for diagnosis, prevention and treatment of hand eczema of the ESCD, stating that moisturizers should be applied on the hands during the working day and especially after work and before bedtime . Interestingly, almost half of the HCWs (46% and 50%, in respectively, in the IG and in the CG) reported at baseline never using hand creams “after the shift,” which is a “key application time” recommended by the ESCD working group .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In The Netherlands, the guidelines on the prevention of contact dermatitis recommend the use of emollients on a regular basis, and creams are often provided by the employer . Similar recommendations have been proposed by the working group for diagnosis, prevention and treatment of hand eczema of the ESCD, stating that moisturizers should be applied on the hands during the working day and especially after work and before bedtime . Interestingly, almost half of the HCWs (46% and 50%, in respectively, in the IG and in the CG) reported at baseline never using hand creams “after the shift,” which is a “key application time” recommended by the ESCD working group .…”
Section: Discussionmentioning
confidence: 72%
“…Despite the improvement in self‐reported hand cream use in this trial, the electronically monitored cream use of 0.4 events per HCW per shift in the IG remained below the recommended frequency of at least two times per shift. As more than one third of HCWs reported that, apart from electronic dispensers, they (also) used their own creams, this electronically measured application frequency might be somewhat underestimated, but it is still probably below the current recommendations of two to three times per day …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…For many years, work‐related skin diseases were leading the list of notifications of suspected occupational diseases in Germany (http://www.dguv.de) in spite of intensive primary and secondary prevention measures . High incidence rates of hand eczema and a tendency to become chronic lead to high costs.…”
Section: Introductionmentioning
confidence: 99%